Pengembangan UKM Online untuk Meningkatkan Kesejahteraan Keluarga Prasejahtera di Makassar - Hasnawiya Hasan; Rahimuddin -; A. Haris Muhammad; Baharuddin - (Faculty of Engineering UNHAS, 2019)
LKSA prasejahtera is a group of mothers who have todlers with poor phisically growth due to their poor daily nutrition. Those children’s problems because of their parents have low income and cannot suport their family. Therefore, the purpose of our program is to help them build an UKM online in order to help them increase their income. This UKM-online is very suitable for their business because of affordable for them compare with the conventional business. These people in the LKSA group do not need rent a place to run their business anymore so they can save more money as we know that the price to rent a strategic place is very high. Howevert, they still can able to run their business and reach more people even they do not have a strategic place. So the website able to help any kind of business because of it provide more detail about their product to many people in unlimeted range. However, this method still needs an expertice in website development in order to build an UKM websites.There are, three type of web developer which are front-end developer, back-end developer,and full-stack developer. Each of web developer has a different function and duty. While, programming language that usually is used in website programming which are, HTML,CSS, Javascript, PHP,and Java. Therefore, the output of this program is expected to be the progress of the business by utilysing an ukm-website. So the underpriviliged people are extpected able to increse their income as well as able to run their business eficient and easy.While, people outside of the LKSA also can take benefit from this ukm-online, because their eficiency of time, place,and budget is also increase and that will make their life more easy and less stress.